Influence of n-6 and n-3 polyunsaturated fatty acids on the resistance to experimental tuberculosis - Paul-Buck, Karl; Leichsenring, Michael; Pfisterer, Matthias; Mayatepek, Ertan; Wagner, Dirk; Domann, Matthias; Sonntag, Hans-Günther; Bremer, Hans J. (Metabolism, 1997)
It has previously been shown that the n-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (20:5(n-3)) and docosahexaenoic acid (22:6(n-3)) possess antiinflammatory properties and can interfere with immune functions. To evaluate whether this would affect resistance to infection, we studied the influence of different types of fatty acids (FAs) on experimental tuberculosis in an animal model. Three groups of 26 weanling guinea pigs were fed isocaloric diets with 26 cal% fat that differed in FA composition with respect to saturated FAs, linoleic acid (18:2(n-6)), eicosapentaenoic acid (20:5(n-3)), and docosanexaenoic acid (22:6(n-3)) as follows: (1) reference (REF) group: 14.8 cal% saturated FAs and 2.8 cal% linoleic acid; (2) n-6 group: 4.6 cal% saturated FAs and 15.4 cal% linoleic acid; (3) n-3 group: 6.3 cal% saturated FAs, 10 cal% linoleic acid, 1.4 cal% eicosapentaenoic acid, and 0.9 cal% docosahexaenoic acid. After 13 weeks, 18 animals from each group were intramuscularly injected with 180 colony-forming units (CFU) Mycobacterium tuberculosis strain H37Rv. Eight noninfected animals per group served as controls. Seven weeks later, the mean number of mycobacteria recovered from the spleens of the n-3 group (log 4.34 CFU, standard error of the mean [SEMI], 0.12) was significantly higher than from the REF group (log 3.90 CFU; SEM, 0.15) and the n-6 group (log 3.93 CFU; SEM, 0.13; P < .05). In addition, the Root Index of Virulence (RIV) showed the most pronounced progression of the disease in the n-3 group. The mean size of the tuberculin reaction was larger in the n-3 group than in the other groups (P < .05). There was no significant difference between the n-6 group and the REF group. We conclude that supplementing the diet with n-3 FAs eicosapentaenoic acid and docosahexaenoic acid can affect resistance to M tuberculosis, whereas supplementing with n-6 FAs does not.
Elektronische Reproduktion der Druck-Ausgabe 31. August 2004
Gesehen am 20.06.2024